Involvement of the 12th Grade English Language Textbook in Jordan: An analytical Study - Abu Saaleek, Rami Ali (Universitas Jambi, Magister Program of English Education Department, 2018)
This study aimed at investigating the involvement of the 12th grade English language textbook in Jordan through analyzing the presentation of educational content and the activities. To achieve this purpose, Romys method was used to calculate the students involvement coefficients. 15% of the book pages were chosen randomly to calculate the involvement of the educational content, and choosing all the activities with total (136) activities. The findings of the study showed that decrease of students involvement in educational content in the English language textbook for 12th grade and did not find within the satisfactory range adopted by Romys, reaching the value to (0.18). The findings of the study also showed that the involvement degree of the activities is excellent with a coefficient (1.41). Recommendations were put forth.